PROSES PENEMPATAN PEGAWAI NEGERI SIPIL DI DINAS PERKEBUNAN PROVINSI KALIMANTAN BARAT - Hakim E.01108006, Arwin Amru (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this article is cent Placement Civil Servants In the Plantation Office of West Kalimantan Province. The article was based on the placement error Plantation Office of the Civil Service of West Kalimantan Province in General and Administrative Section, An error in the placement of the Civil Service Office of West Kalimantan Plantation In Marketing Section. From both these problems, will greatly affect the activity and human resource management activities in particular in achieving organizational goals or government. This in turn will affect the human resource management employee less than optimal. The formulation of the problem is presented in order to clarify the objectives contained in this research, in particular that this study does not deviate from the predetermined target more, especially in collecting data in the field. Thus the formulation of this problem is: "Why Error Occurred In The placement process (Staffing) Civil Servants In the Plantation Office of West Kalimantan Province". The method used in this study was a descriptive study with a qualitative approach where in solving the problems examined do to give you an idea what it is in accordance with the reality on the ground. Purpose of this article is to provide an understanding of the placement of the Civil Service in Plantation Office of West Kalimantan Province. Issues regarding Why Error Occurred In process and why things go wrong in Placement (Staffing) Civil Servants In the Plantation Office of West Kalimantan Province.Data analysis shows the occurrence of errors in the placement of the Civil Service in West Kalimantan Plantation Office, due to the employee who is approaching retirement who have been filling the position, but his experience and is often followed that training. It should be given to more effective training for employees to non-technical so that it can run smoothly and effectively and should be a synchronization between the Provincial Government SBKA with the Placement Office Employees that can suit the needs of employees and positions that are vacant.Keywords: Placement Errors Employees, Employee Training.